Algal and invertebrate responses to atmospheric nitrogen deposition in Rocky Mountain lakes - Lafrançois, Brenda Moraska, author; Johnson, Brett, advisor; Baron, Jill S., advisor; Kondratieff, Boris C., committee member; Covich, Alan P., committee member (Colorado State University. Libraries, 2002)
In a series of lake surveys and experimental studies we explored how excess nitrogen, alone and in conjunction with phosphorus and/or acid, affects structural and functional aspects of mountain lake ecology in the Colorado Front Range and Wyoming Snowy Range. Our survey of Front Range lakes examined relationships between benthic invertebrate assemblages and environmental characteristics and found that benthic invertebrate composition among lakes was related more to elevation gradients and the presence of fish than to nitrogen or other water chemistry gradients. To understand how increased nitrogen could affect other lake biota (algae, zooplankton) and lakes with low nitrogen, we conducted mesocosm experiments in two Snowy Range lakes. We found that N and N+P additions caused eutrophication responses ranging from increased algal biomass and productivity to marked shifts in phytoplankton composition. Our survey of water chemistry, nutrient ratios and phytoplankton composition in fifteen Snowy Range lakes showed that N regulation of phytoplankton growth and composition may predominate regionally; nitrate and DIN:TP levels were generally low among Snowy Range lakes and phytoplankton composition was tightly linked to N chemistry. Because excess N can lead to both eutrophication and acidification, we conducted mesocosm experiments in a high-nitrate Front Range lake and a low-nitrate Snowy Range lake to examine responses of lake biota to simultaneous nutrient and acid additions. We found that nutrients and acid altered phytoplankton composition in both lakes, favoring chlorophyte taxa in the low-nitrate lake, and chlorophytes and the dinoflagellate Gymnodinium in the high-nitrate lake. Changes in algal biomass were tightly linked to nutrient additions; changes in species composition were related to both nutrients and pH. Overall, zooplankton and benthic algal communities showed inconsistent responses to nutrient or nutrient+acid additions in our mesocosm experiments and may be poorer early indicators of enrichment and acidification than phytoplankton. We conclude that eutrophication effects of N deposition are most likely in low-nitrate lakes such as those of the Snowy Range, and that effects of N and acidification would likely be strong and interactive in lakes of both the Front Range and Snowy Range.
Keywords: ecology; freshwater ecology; environmental science; limnology